In-plane displacement measurement in vortex metrology (2013)
Recently we proposed an alternative method of displacement analysis in vortex metrology, based on the application of the Fourier optics techniques, that is suitable for an intermediate range of displacement measurements ranging below the resolution of speckle photography and above that of the conventional vortex metrology. However, for smaller displacements, we introduce an approach to perform the Fourier analysis from vortex networks. In this work, we present an enhanced method for measuring uniform in-plane displacements, taking advantage of the capability of determining the subpixel locations of vortices and having the ability to track the homologous vortices onto a plane. It is shown that high-quality fringe systems can be synthesized and analyzed to accurately measure in an extended range of displacements and for highly decorrelated speckle patterns. Experimental results supporting the validity of the method are presented and discussed. © 2013 Optical Society of America